The Effectiveness of Empathy and Problem-Solving Skills Training on Social Self-efficacy and Mental Security of High School Boys - Zarei, Adel; Makvandi, Behnam; Ehtesham Zadeh, Parvin; Bavi, Sasan (International Clinical Neuroscience Journal, 2022)
Background: Teaching empathy and problem-solving skills is effective in improving students’ self-efficacy and quality of social life. We aimed to compare the effectiveness of empathy and problem-solving skills training on social self-efficacy and psychological security of Assaluyeh second high school boys. Methods: This was a quasi-experimental study on all male high school students in Assaluyeh in the academic year of 2019-2020, of whom 45 were purposefully selected and assigned to two experimental groups and controls group. One experimental group received empathy training and the other group received problem-solving training in eight 90-minute sessions. To collect data, the social self-efficacy and Maslow’s psychological security questionnaires were used. Analysis of covariance was done using SPSS-24 software. Results: Empathy and problem-solving training were effective on social self-efficacy and psychological security of high school boys (P < 0.001). Also, no significant difference was found between the effectiveness of empathy skills training and problem-solving training on social self-efficacy and psychological security (P < 0.746). Conclusion: Empathy and problem-solving training increased social self-efficacy as well as psychological security in high school boys.